Analisis Penerapan Sistem Pembayaran Quick Response Code Indonesian Standard (QRIS) pada Kantin Baru Universitas Negeri Jakarta - Witanti Putri Anggreani; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
In the era of digitalization and rapid technological development, payment systems have undergone significant transformation. One innovation in payments is the Quick Response Code Indonesian Standard (QRIS), which has become increasingly common in various sectors. An in-depth understanding of the implementation of QRIS in the new canteen environment of Jakarta State University will provide valuable insight into how this new technology impacts the transaction process. This research uses a qualitative descriptive approach, namely by describing and analyzing the problems found. Data collection techniques are based on primary data and secondary data. Primary data in this research was obtained by conducting observations, interviews, and documentation, while secondary data was obtained through books, previous research, and articles related to research. The purpose of this research is to evaluate the extent to which the implementation of QRIS in the New Canteen at Jakarta State University has succeeded in achieving the initial goal of improving the payment process, understand the positive impacts that have been generated by the use of QRIS, including increased efficiency, transaction security and convenience for users, and identify obstacles. that may arise in implementing QRIS, such as network problems or additional costs, which may affect its effectiveness. From the results of this research, it can be seen that the implementation of QRIS in the New Canteen at Jakarta State University has gone well even though several obstacles need to be corrected, such as a lack of consistency in payment rules and a lack of socialization about QRIS. The Policy and Use of QRIS in the new canteen at Jakarta State University has succeeded in achieving order, efficiency, and security in the payment process, simplifying transactions, reducing dependence on cash, reducing the risk of errors, and increasing sales in the canteen. Although there are challenges such as network problems, inadequate smartphones, and administration costs. It is highly recommended that sellers and managers of the New Jakarta State University Canteen continue to implement quality improvements properly. It is necessary to carry out intensive outreach to students and canteen staff regarding QRIS and how to use it, and it is important to ensure that the QRIS system runs smoothly and safely. Thus, the implementation of QRIS in the New Canteen at Jakarta State University provides significant benefits and has the potential to continue to be improved.